Investigate the potential demand of Chinese senior tourists in their decision making to travel - Xi, Wei (2020)
The ageing population was a common phenomenon in the majority of countries in the world after baby boomer generation. Driven by the size of the baby boomer generation, population ageing is likely to affect the future choice of tourism activities and destinations. As the baby boomers retire, their demand patterns and preferences will grow in significance and will strongly influence the future structure of tourism product development. Senior or elderly market in all industry is popular because their high demand, senior tourism is already not a new concept introduced, it have been a palmy industry for the economic growth. The aim of the research is to identifying the senior tourism market and their profiles, preferences, and motivation, to analyze the potential demand patterns among different senior tourists group, as well to investigate the market strategies to transfer the potential demand into effective demand. Thus, a total of 100 respondents have been selected through purposive sampling technique where most of them are from older population between 55 - 70 years old. The finding show that senior tourist have different tourism preference based on their characteristic, there are the high demand for special tourism service and product to meet the demand of senior tourist. Therefore, this study contributed investigate the senior traveler’s motivation and travel preference, in further to analyze their tourism demand.